Discovery of novel materials with broad resistance to bacterial attachment using combinatorial polymer microarrays - Hook, Andrew L.; Chang, Chien-Yi; Yang, Jing; Atkinson, Steve; Langer, Robert; Anderson, Daniel G.; Davies, Martyn C.; Williams, Paul; Alexander, Morgan R. (Wiley, 2013)
A new class of bacteria-attachment-resistant materials is discovered using a multi-generation polymer microarray methodology that reduces bacterial attachment by up to 99.3% compared with a leading commercially available silver hydrogel anti-bacterial material. The coverage of three bacterial species, Pseudomonas aeruginosa, Staphylococcus aureus, and uropathogenic Escherichia coli is assessed.